Octreotide Protects the Mouse Retina against Ischemic Reperfusion Injury through Regulation of Antioxidation and Activation of NF-κB. (14th June 2015) - Wang, Jun; Sun, Ziqiang; Shen, Junsheng; Wu, Dongdong; Liu, Fang; Yang, Ruisheng; Ji, Shaoping; Ji, Ailing; Li, Yanzhang
Abstract : Somatostatin (SST), an endogenous peptide, may exert anti-inflammatory and neuroprotective effects on retinal injury induced by ischemia. Retinal ischemic reperfusion (I/R) injury always produces many reactive oxygen species (ROS), which can aggravate the tissue damage. The effects of octreotide (OCT), a SST analogue, on retinal I/R injury and ROS formation, are not very clear. In this study, we observed the effects of OCT on morphological changes, oxidative stress, and cell death, induced by retinal I/R injury. The activation of nuclear factor κ B (NF- κ B) and intercellular adhesion molecule-1 (ICAM-1) were further evaluated in I/R retina treated with or without OCT. The retinal layer thickness was increased at 1 day after I/R and decreased at 7 days after I/RP < 0.05 . This effect was associated with increase in MDA and ROS levelsP < 0.05 . The Tunel-positive cells increased and the number of ganglion cell layer (GCL) neurons decreased significantly after I/R injury. The expression of p-p65 and ICAM-1 increased significantly in I/R retinasP < 0.05 . Each effect was markedly attenuated by application of OCT. These data indicate that OCT protects the retina against retinal I/R damage, which could be through inhibition of oxidative stress and downregulation of NF- κ B and ICAM-1 expression.